Valproate effect on ketosis in children under ketogenic diet. (July 2016) - Spilioti, Martha; Pavlou, Evangelos; Gogou, Maria; Katsanika, Irene; Papadopoulou-Alataki, Efimia; Grafakou, Olga; Gkampeta, Anastasia; Dinopoulos, Argyrios; Evangeliou, Athanasios
Abstract: Introduction: Although ketogenic diet has been proven useful in the management of intractable seizures, interactions with other medicines have been reported. This study reports two patients on co-administration with ketogenic diet and valproate appearing undesirable side effects after increase or decrease of valproate pharmaceutical levels. Methods: Totally 75 patients suffering from drug-resistant epilepsy were treated with ketogenic diet in our departments. Their age varied from 6 months to 9 years. All patients were followed for at least 12 months and up to five years. Clinical and laboratory variables have been regularly assessed. Results: In 75 patients treated with ketogenic diet and valproate at the same time treatment was well tolerated. Two patients presented mild to moderate undesirable effects. In these patients the removal of valproate treatment resulted in an increase of ketosis with respective clinical signs. The conversion of the diet from 4:1 to 1:1 and 2, 5:1 respectively resulted in reduction of ketosis and clinical improvement. Conclusion: In the majority of cases co-administration of valproate and ketogenic diet seems to be safe. In two cases, valproate appeared to have a negative effect on ketosis (and weaning it led to over-ketosis). This interaction is worthy of future study. Highlights: We present our experience about co-administration of ketogenic diet and valproate. Totally 2/75 patients experienced mild to moderate adverse events. Side effects were mainly related to the intermediary metabolism of each person. Adverse events when co-administering ketogenic diet and valproate are rare. Changes in ketosis level should always be considered.